Male-killing bacteria in insects: mechanisms, incidence, and implications. - Hurst, G D (Centers for Disease Control and Prevention, 2000)
Bacteria that are vertically transmitted through female hosts and kill male hosts that inherit them were first recorded in insects during the 1950s. Recent studies have shown these "male-killers" to be diverse and have led to a reappraisal of the biology of many groups of bacteria. Rickettsia, for instance, have been regarded as human pathogens transmitted by arthropods. The finding of a male-killing Rickettsia obligately associated with an insect suggests that the genus' members may be primarily associated with arthropods and are only sometimes pathogens of vertebrates. We examined both how killing of male hosts affects the dynamics of inherited bacteria and how male-killing bacteria affect their host populations. Finally, we assessed the potential use of these microorganisms in the control of insect populations.